Needs Analysis Development of SSI-Based E-Modules on Ecology and Biodiversity Materials to Empower Students' Creative Thinking Skills - Hartanto, Budi; Prayitno, Baskoro Adi; Indrowati, Meti (Journal of Educational Sciences, 2025)
Creative thinking skills are important for students to develop innovative solutions. One of the learning approaches in Natural Sciences that is effective for training creative thinking is the SSI (Socio-Scientific Issues) approach. The purpose of the research was to analyze the needs of teachers and students in the development of SSI-based e-modules to empower students' creative thinking skills. Data were collected through questionnaires given to four science teachers and 119 seventh grade students from four schools located in Wonogiri, Sukoharjo, Klaten, and Gunungkidul districts. The results showed that 1) 75% of teachers have difficulties in learning science. 2) 100% of teachers feel limitations in teaching materials. 3) 75% of teachers need teaching materials that can help teach science concepts. 4) 100% of teachers agree with the development of SSI-based e-modules. 5) 54% of students feel there is something incomplete with the module used. 6) 52% of students have difficulty in learning material from books. 7) 98% of students have smartphones. 8) 96% of students need SSI-based e-modules. The conclusion of the research shows that teachers and students need SSI-based e-modules on ecology and biodiversity materials that are easily accessible and effective to empower students' creative thinking skills.